Predicting College Students’ Intention to Reject Sexual Violence: The Role of Self-Esteem and Religiosity - Nurfadilah Nurfadilah; Nur Afiah (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2026)
Sexual violence in higher education threatens students’ psychological well-being, academic engagement, and sense of safety. In this study, sexual violence encompasses harassment, coercion, and assault occurring within higher education settings. In Indonesia, the increasing number of reported cases and the persistence of underreporting highlight the urgency of identifying internal factors that shape students’ intention to reject such behavior. Grounded in the Theory of Planned Behavior, this study examined the simultaneous and partial effects of self-esteem and religiosity on students’ intention to reject sexual violence. Using a quantitative approach with multiple linear regression, data were collected from 209 active undergraduate students at IAIN Parepare through validated four-point Likert-scale instruments. The findings indicated that self-esteem and religiosity simultaneously had a significant effect on intention (Adjusted R² = 0.703, p < .001). However, partial analysis revealed that only religiosity had a significant and dominant positive effect (β = 0.829, p < .001), while self-esteem did not show a statistically significant contribution (p = .124). These results suggest that moral and spiritual value internalization plays a more decisive role than positive self-evaluation in shaping students’ commitment to rejecting sexual violence. The study underscores the importance of integrating inclusive religious education with institutional prevention policies to foster a safer campus environment.